Dominasi Istri dalam Rumah Tangga dalam Masyarakat Bebidas Kecamatan Wanasaba Lombok Timur - Diannika Wahyu Hidayah; Muhammad Arifin Badri (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2024)
Saying ’husbands are afraid of their wives’ is no longer a taboo, both in cyberspace and everyday social life. This study aims to analyze the husband’s fear of his wife in the community of Bebidas village, East Lombok, the implications that can be caused to household harmony, as well as knowing the rights and obligations of husband and wife in Islam. this research uses a Qualitative approach with the type of case study. The results showed that the phenomenon of husbands being afraid of their wives in Bebidas village community is only a mere assumption. However, this statement needs to be re-analyzed, because sometimes husbands are too proud to admit it, this can be caused by several factors including the dominance of patriarchal culture. The implications of husbands being afraid of their wives are domestic stress, reduced harmony, leading to divorce and the breakdown of the relationship between parents and children. Meanwhile, the rights and obligations of husband and wife in Islam include the rights and obligations of the husband, the rights and obligations of the wife and joint rights as husband and wife.